QTc evaluation in patients with bundle branch block. (October 2020) - Bogossian, Harilaos; Linz, Dominik; Heijman, Jordi; Bimpong-Buta, Nana-Yaw; Bandorski, Dirk; Frommeyer, Gerrit; Erkapic, Damir; Seyfarth, Melchior; Zarse, Markus; Crijns, Harry J.
Abstract: Proper measurement of the QT interval on the 12-lead body-surface ECG is challenging in daily practice. Even more difficult is its correct estimation in the presence of repolarization abnormalities, arrhythmias or bundle-branch blocks (BBB). The QT interval results from two parts of the ECG: (1) the QRS complex, describing the excitation of the ventricles and (2) the JT interval, describing the repolarisation of the ventricles. Prolongation of the QRS width – like in the presence of BBB – entails prolongation of the QT interval, making the estimation of the true repolarisation time challenging. The US recommendations for the standardization and interpretation of the ECG suggest focusing on the JT interval in presence of BBB. However, in clinical practice physicians have become more familiar with the interpretation of QT-interval measurements than with the interpretation of the JT Interval. In the last decade, a simple formula for the estimation of the "modified QT interval" in the presence of left or right BBB has been developed and evaluated. In this formula, the modified QT interval is calculated by subtracting 50% of the length of the BBB-QRS from the measured QT interval (QTm = QTBBB − 50% QRSBBB ). Subsequently, rate-correction formula should be applied as usual. In this review, we discuss the determination of the QT-interval in the presence of BBB and summarize the origin and application of the modified QT-interval formula.